Distribution of active ingredients of a commercial aflatoxin biocontrol product in naturally occurring fungal communities across Kenya - Islam, Md-Sajedul; Callicott, Kenneth A.; Mutegi, Charity; Bandyopadhyay, Ranajit; Cotty, Peter J. (Wiley, 2021)
Human populations in Kenya are repeatedly exposed to dangerous aflatoxin levels through consumption of contaminated crops. Biocontrol with atoxigenic Aspergillus flavus is an effective method for preventing aflatoxin in crops. Although four atoxigenic A. flavus isolates (C6E, E63I, R7H and R7K) recovered from maize produced in Kenya are registered as active ingredients for a biocontrol product (Aflasafe KE01) directed at preventing contamination, natural distributions of these four genotypes prior to initiation of commercial use have not been reported. Distributions of the active ingredients of KE01 based on haplotypes at 17 SSR loci are reported. Incidences of the active ingredients and closely related haplotypes were determined in soil collected from 629 maize fields in consecutive long and short rains seasons of 2012. The four KE01 haplotypes were among the top ten most frequent. Haplotype H-1467 of active ingredient R7K was the most frequent and widespread haplotype in both seasons and was detected in the most soils (3.8%). The four KE01 haplotypes each belonged to large clonal groups containing 27–46 unique haplotypes distributed across multiple areas and in 21% of soils. Each of the KE01 haplotypes belonged to a distinct vegetative compatibility group (VCG), and all A. flavus with haplotypes matching a KE01 active ingredient belonged to the same VCG as the matching active ingredient as did all A. flavus haplotypes differing at only one SSR locus. Persistence of the KE01 active ingredients in Kenyan agroecosystems is demonstrated by detection of identical SSR haplotypes six years after initial isolation. The data provide baselines for assessing long-term influences of biocontrol applications in highly vulnerable production areas of Kenya.